The behaviour of the MPC: Gradualism, inaction and individual voting patterns - Charlotta Groth; Tracy Wheeler (Bank of England, External Monetary Policy Committee Unit, 2008)
We evaluate the degree of gradualism and inaction in UK monetary policy over the Monetary Policy Committee (MPC) period (1997-2007) at the quarterly and the monthly frequency. After accounting for misspecification in standard Taylor rules, we find little evidence for gradualism. A measure of optimal policy is calculated. Comparing this with actual policy suggests that there is less inaction in monetary policy decisions than previous work suggested for the period prior to the formation of the MPC. In an analysis of the MPC's monthly voting decisions, we find that the activity rate, defined as the probability that the MPC vote to change interest rates in a given month, has fallen over time. This reflects the increased stability of inflation and output growth, rather than changes in the degree of gradualism and/or inaction. There is some evidence for inaction at the monthly frequency however, demonstrated by the fact that the MPC is more active in the forecast month than in the non-forecast month. The MPC also tends to wait longer before reversing the direction of interest rate changes than continuing them. This difference appears not to be driven by gradualism, and so provides further evidence for inaction at the monthly frequency. A panel data analysis suggests that the MPC as a whole is equally active as its individual members, so inaction appears not to be driven by the use of a committee to set monetary policy. There is no evidence that activity rates fall with the length of time that a member has served on the committee, suggesting that learning about the transmission mechanism has no impact on the tendency for gradualism and inaction.
Keywords: D78; E43; E52; 330; Monetary Policy; Taylor Rules; Voting Patterns; Zentralbank; Führungsorganisation; Gruppenentscheidung; Wahlverhalten; Geldpolitik; Großbritannien